P226 Reattendance, retesting and test positivity among patients initially treated for chlamydia or gonorrhoea in a large inner city clinic. (30th June 2016) - Bradley, Sarah; Saunders, John; Jungmann, Eva
Abstract : Background/introduction: Reinfection with a bacterial sexually transmitted infection following treatment is common. National guidelines recommend retesting for chlamydia three to six months after treatment in <25 year olds. Aim(s)/objectives: To review reattendance, retest and positivity rates in patients with chlamydia or gonorrhoea at a large inner-city clinic. Methods: Patients diagnosed with chlamydia or gonorrhoea were identified in our electronic patient records (March-September 2015). Proportion reattending, retesting and test positivity two to four months after treatment of the initial infection were recorded. Results: The minority of patients treated for chlamydia and gonorrhoea reattended and retested for infection (Table 1 ). Positivity was high in those who retested, especially in MSM. Two HIV diagnoses and 89 syphilis serology positive results were found in those retesting. Discussion/conclusion: Retesting rates following treatment for chlamydia and gonorrhoea are low. Those who did reattend and retest experienced high rates of infections and represent an important group to target for active recall.